Inheritance pattern of molar-incisor hypomineralization - Jeremias, Fabiano [UNESP]; Bussaneli, Diego Girotto [UNESP]; Restrepo, Manuel; Pierri, Ricardo Augusto Gonçalves [UNESP]; Souza, Juliana Feltrin de; Fragelli, Camila Maria Bullio [UNESP]; Secolin, Rodrigo; Maurer-Morelli, Claudia Vianna; Cordeiro, Rita de Cassia Loiola [UNESP]; Scarel-Caminaga, Raquel Mantuaneli [UNESP]; Santos-Pinto, Lourdes [UNESP] (FapUNIFESP (SciELO), 2021)
The aim of this study was to investigate the segregation patterns of molar incisor hypomineralization (MIH) in families, given the evidence that its etiology is influenced by genetics. Clinically, MIH may be detected in parents and/or siblings of MIH-affected children. Our study included children with at least one first permanent molar affected by MIH (proband) and their first-degree relatives (parents and siblings). The participants were examined clinically to detect MIH, according to the European Academy of Paediatric Dentistry criteria (2003). A total of 101 nuclear families (391 individuals) were studied. Proband diagnosis was followed by MIH classification of the subject, his parents and siblings, as affected, unaffected, or unknown. Segregation analysis was performed using the multivariate logistic regression model of the Statistical Analysis for Genetic Epidemiology package, and segregation models (general transmission, environmental, major gene, dominant, codominant and recessive models). The Akaike information criterion (AIC) was used to evaluate the most parsimonious model. In all, 130 affected individuals, 165 unaffected individuals, and 96 unknown individuals were studied. Severe MIH was found in 50.7% of the cases. A segregation analysis performed for MIH revealed the following different models: environmental and dominance (p = 0.05), major gene (p = 0.04), codominant (p = 0.15) and recessive models (p = 0.03). According to the AIC values, the codominant model was the most parsimonious (AIC = 308.36). Our results suggest that the codominant model could be the most likely for inheriting MIH. This result strengthens the evidence that genetic factors, such as multifactorial complex defect, influence MIH.